Spatiotemporal Variation in Presummer Precipitation Over South China From 1979 to 2015 and Its Relationship With Urbanization. Issue 13 (3rd July 2019) - Su, Lin; Li, Junlu; Shi, Xiaoming; Fung, Jimmy C. H.
Abstract: The variation in presummer precipitation in South China from 1979 to 2015 and its relationship with urbanization were analyzed. The results reveal that the intensity of precipitation and the occurrence of extreme precipitation events during the presummer season in South China have increased significantly, and the upward trend is much more significant in urban areas than in nonurban areas. The mean trends in urban and nonurban areas in South China are, respectively, 1.34 and 0.97 mm/day/year for maximum daily precipitation, 4.41 and 2.79 mm/year for the top 5% of daily precipitation, and 0.26 and 0.16 day/year for extremely heavy precipitation days during the presummer season. In addition to the variability of large‐scale atmospheric circulation, urbanization appears to have a significant effect on the variability of presummer precipitation in South China, especially with regard to the intensity of precipitation and the occurrence of extremely heavy precipitation. From 1979 to 2015, the upward trends of maximum daily precipitation, the top 5% of daily precipitation, and extremely heavy precipitation days during presummer season in urban areas are, respectively, between 38.14% and 39.18%, 55.97% and 59.14%, and 43.75% and 68.75% higher than those in nonurban areas during the investigated period. Urban areas in South China are more exposed to extreme precipitation than nonurban areas during the presummer season. Key Points: The presummer precipitation over South China had undergone a drastic intensification between 1979 and 2015 The increasing trend was much more significant in urban areas than in nonurban areas The effects of urbanization on the intensification of the presummer precipitation over South China were analyzed and discussed